Experimental Swing-Up Control of Advanced Sliding and Energy-based Modes for Pendubot - Tran, Minh-Duy; Trinh, Minh-Phu; Do, Nguyen-Son; Phan, Thai-Chan; Ngo, Tan-Bao-Chau; Nguyen, Viet-Thuan; Ngo, Viet-Dung; Hoang, Ngoc-Quan; Trinh, Tan-Phong; Le, Thi-Hong-Lam (Journal of Fuzzy Systems and Control, 2025)
This study focuses on the implementation and comparative evaluation of two swing-up control strategies—Energy-Based Methods (EBM) and Advanced Sliding Mode Control (ASMC)—for pendubot, a nonlinear two-link robotic system. While previous research has extensively explored balancing algorithms for this model, swing-up strategies have primarily been analyzed through simulations, with limited application to real-world systems. This research addresses this gap by deploying both EBM and ASMC on a physical pendubot model. Practical results are presented to provide the most accurate evaluation of the control quality of each algorithm.